IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS PROYEK PADA MATERI KLASIFIKASI MAKHLUK HIDUP UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VII SMP AL-AZHAR - Andiyanti, Agnes Intan; Fatimah, Fita; Maharani, Lila (Universitas Khairun, 2025)
Research This study aims to improve student learning outcomes through the application of a project-based learning model. (project-based learning) in the subject of Science subject in class VII of AL-AZHAR Junior High School. Background of this research This research is the low learning outcomes of students where as many as 51.85% students scored below the KKM (70). This is caused by the lack of interest and motivation to learn and motivation to learn. This research is a Classroom Action Research (PTK) which was carried out in two cycles with each cycle consisting of the following stages stages of planning, implementation, observation, and reflection. The research subjects were seventh grade students of AL-AZHAR Junior High School totaling 27 students. Data collection techniques data collection techniques were conducted through learning outcome tests, observation, and documentation. Results The results showed that the application of project-based learning model can improve student learning outcomes in each cycle, namely the pre-cycle average value of 72.81 with a percentage of completeness of 48.81. cycle average value of 72.81 with a completeness percentage of 48.15% increased in cycle I with an average of 72.48 with a 66.15% completeness percentage. cycle I with an average of 72.48 with a completeness percentage of 66.67%, and in cycle II with an average of 78.92 with a completeness percentage of 48.15%. cycle II with an average of 78.92 with a completion percentage of 85.18%. With Thus, the project-based learning model was declared successful to improve student learning outcomes in the classroom.